Metode Peer Assisted Learning terhadap Pengetahuan dalam Upaya Mencegah Kekerasan Seksual Remaja - Mohamad Wahyu Kasim; Vivien Novarina A. Kasim; Nirwanto K. Rahim (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the effect of peer-assisted learning on knowledge in preventing sexual violence among adolescents. The method employed was a quantitative approach, utilizing a pre-experimental research design and an intact-group comparison design. Bivariate analysis was performed using the Wilcoxon signed-rank test and the Mann-Whitney U-test. The results showed a p-value of 0.000 for the intervention and control groups. The Mann-Whitney test showed an effect of peer-assisted learning on knowledge of sexual violence (p = <0.05), with the intervention group having a mean score of 37.37 and the control group 17.63. Thus, there is a difference in knowledge of sexual violence between the intervention and control groups. In conclusion, the peer-assisted learning method affects knowledge in preventing sexual violence among adolescents at SMPN 1 Gorontalo City. Keywords: Sexual Violence, Peer-Assisted Learning, Adolescents